Training for Imams and Makmum to Pray Perfectly in Sanad as Guided by the Prophet Muhammad by Dr. Kh. M. Sholeh Qosim, M.Si as Da'wah Communication - Basir, Abdul; Rahman, Dicky Nur; Qona’ati, Arini Fahma; Aziz, Moh. Ali (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to explain the process of da'wah communication through training for Imams and Makmum to perform perfect prayers in Sanad according to the guidance of Rasulullah SAW and using descriptive qualitative methods by studying in depth and data collection techniques carried out by triagulation. The research results and discussions explain charity without knowledge will be in vain, and true knowledge must be obtained through teachers who have sanad, which is the chain of transmission of knowledge from Rasulullah SAW to today's ulama. A da'i acts as an active communicator and agent of change, so that the message of da'wah can be felt significantly by the community. Training is an effective da'wah model that allows direct interaction between the communicator and the communicant so that the da'wah material can be delivered thoroughly